2012
DOI: 10.1111/j.1365-2125.2012.04302.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of venous thromboembolism prophylaxis with fondaparinux or low molecular weight heparin in a large cohort of consecutive patients undergoing major orthopaedic surgery – findings from the ORTHO‐TEP registry

Abstract: WHAT IS ALREADY KNOWN ABOUT THE TOPIC• Patients undergoing major orthopaedic surgery are at high risk of venous thromboembolism.• Medical thromboprophylaxis is effective to reduce this risk and in large trials, fondaparinux proved superiority over low molecular weight heparin (LMWH) in this indication with the downside of higher complication rates.• Patients in clinical trials are a selected subpopulation and efficacy and safety results need to be confirmed in large cohorts of unselected patients.WHAT THIS STU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 27 publications
0
10
1
Order By: Relevance
“…All patients undergoing MOS at the Orthopaedic Department of the University Hospital in Dresden, Germany, between January 2006 and June 2011, were included in the ORTHO‐TEP registry. A detailed description of the registry design has previously been published [12]. In brief, all patients undergoing major orthopedic surgery are prospectively entered in a quality management database.…”
Section: Methodsmentioning
confidence: 99%
“…All patients undergoing MOS at the Orthopaedic Department of the University Hospital in Dresden, Germany, between January 2006 and June 2011, were included in the ORTHO‐TEP registry. A detailed description of the registry design has previously been published [12]. In brief, all patients undergoing major orthopedic surgery are prospectively entered in a quality management database.…”
Section: Methodsmentioning
confidence: 99%
“…Fondaparinux can be used as an alternative to UH or LMWH in the majority of indications for antithrombotic treatment or prophylaxis, in patients with competent renal function, by once-daily subcutaneous delivery without the need for laboratory monitoring (Garcia et al, 2012). For example, efficacy and safety of fondaparinux have been found to be comparable with intravenous UH in the treatment of PE (Büller et al, 2003), LMWH in VTE prophylaxis after major orthopedic surgery (Donath et al, 2012), and LMWH in non-STEMI, whereby bleeding risk was found to be lower with fondaparinux (Szummer et al, 2015). Fondaparinux is reported to have been used successfully during pregnancy in the case of hypersensitivity to heparin (Elsaigh et al, 2015), but it is not currently recommended because of the lack of safety data in this setting .…”
Section: E Fondaparinux and Other Alternativesmentioning
confidence: 99%
“…Nonetheless, risk of death from VTE was found to be very low in patients managed with modern anticoagulant regimens, including enoxaparin, in the trials analyzed in a recent systematic review (Chan et al, 2015), and routine pharmacological thromboprophylaxis is recommended in the majority of patients undergoing major orthopedic procedures (Falck-Ytter et al, 2012). While presenting a considerable risk in itself, the presence of additional risk factors in patients undergoing major surgery may further increase the likelihood of significant thrombosis; a large retrospective cohort study of patients who had undergone major orthopedic surgery found that female sex and a previous history of VTE were the major determinants of thrombosis risk in this setting (Donath et al, 2012). …”
Section: Clinical Use As An Anticoagulant/ Antithromboticmentioning
confidence: 99%
“…ORTHO-TEP registry compared the efficacy and safety of fondaparinux and LMWH in 3819 patients undergoing major orthopaedic surgery [16]. The main limitation of the study was its retrospective nature and the comparison of two different periods, the first in which LMWH ( 3000-6000 aX U) and in the second with fondaparinux 2.5 mg used as thromboprophylaxis ,.…”
Section: Fondaparinuxmentioning
confidence: 99%
“…Female sex and previous DVT were the more relevant risk factors for DVT independently from the drug used for pharmacological prophylaxis in the ORTHO-TEP study [16] . In a study by Kang et al [17] DVT was detected by B-mode ultrasonography performed 7 days after TKR in 175/1025 patents aged >75 years.…”
Section: Pathophysiologymentioning
confidence: 99%